Inflation, inflation uncertainty and output growth: what does the data say for Malaysia? - Baharumshah, Ahmad Zubaidi; Soon, Siew Voon (Emerald Group Publishing Limited, 2014)
Purpose: The purpose of this paper is to examine the causal relationships between inflation, output growth and their uncertainties in Malaysia.Design/methodology/approach: The modeling approach allows for structural breaks to avoid the masking of specific impacts. Findings: Based on the asymmetric Generalized Autoregressive Conditional Heteroskedasticity model, the paper found strong evidence favoring a positive effect of a change in the inflation uncertainty as predicted by the Friedman-Ball hypothesis. In addition, inflation (inflation uncertainty) has direct (indirect) negative effect on the output growth. The results are consistent with the Taylor effect – increases in inflation uncertainty decreases output uncertainty. The analysis also reveals that economic uncertainty lowers the growth rate of output, complying with Bernanke's idea. Originality/value: The present study suggests that extra efforts are required to locate the breaks in the variance in order to draw concrete evidence on link between economic uncertainty and macroeconomic performance.